Avaliação do Serviço de Atendimento Móvel de Urgência na atenção aos acidentes de trânsito na zona urbana de Sobral - CE - Dias, Lívia Karla Sales (2016)
The traffic violence involves millions of people, it becomes a great public health problem, taking the young people´s lives away and it´s responsible for high expenses in Health. Many health services are involved in the assistance of the traffic injured people, among them, The Mobile Emergency Medical Services (SAMU) which provides first-line treatment to the these ones, helping them to minimize their permanent physical injuries. The study aims at assessing the Mobile Emergency Medical Services' support to traffic victims in Sobral-CE, using Donabedian´s theoretical background, with both qualitative approaches, under the focus of Donabedian´s evaluation of the structure, process and results from the The Mobile Emergency Medical Services (SAMU) in Sobral-CE. 14 people from this service took part in the research, in which 2 were managers of this service and three were workers from each category: doctors, nurses, nursing technicians and conductors. A questionnaire about the human and physical structure was applied to the managers, a focus group about the process of work was carried out to the assistance professionals and, about the results, the medical reports of traffic victims treated by SAMU in 2014 were reviewed. The quantitative data were processed in the 2010 Excel Microsoft Office, creating graphics as well as a map of the traffic accidents was done using the QGis 2 program, the qualitative ones were submitted to content analysis from the thematic type proposed by Minayo. This research respected the bioethical principles described on the Resolution 466/12 of the National Health Council and approved by the Ethics Committee on research under the protocol number 1,320,647.In the investigation about the structure we identified that the material resources and sufficient ambulances, with a radio communication failure, with a proper number of professionals in the base and a Regulation Center. In the process analysis we noticed that the nurses have more time on duty than the other workers, who have revealed to be unsatisfied because of the structure offered to the traffic accidents, reporting a poor performance on the permanent education. They were professionally unhappy due to the fragile employment relationship, the absence of labor rights, poor salaries and the respect of the employee´s integrity, they suggest improvements on the traffic victim treatment. There were 89,58 injured people per month, with the maintenance of the number during months, highlighting the accidents involving motorcycles, mainly the falls from them. The accidents attacked more male youths and ambulances of basic support were sent most of the times, what characterizes accidents of low severity, which were taken to the Reference Hospital of trauma in 91% of the incidents. The weekdays mornings and the weekend nights were responsible for the majority of the accidents. The most affected neighborhoods were Downtown, Junco, Sinhá Sabóia in decreasing order. In order to reduce these aggravating numbers, we understand that traffic education combined with rigid inspection to many reckless occurrences and structural improvements are necessary to increase the mobility of vehicles and pedestrians from the city, permitting a wholesome traffic.